بچوں کے ادب میں تہذیب و تشخص کا اظہار:تحقیقی مطالعہ: Expression of Culture and Identity in Children's Literature: An Exploratory Study - بانو, ڈاکٹر فضیلت (Tashkeel e Jadeed, 2024)
The long journey of children's literature in Urdu has passed through various phases. Fist it encompasses the aesthetic and cultural colors and the cultural beauty is seen in the next stage. Over time, this literature, which started with simple and easy-to-understand stories, began to contain the element of constructive and creative development. After the independence war of 1857, the realization of local civilization was made part of this body of literature. There are many names in this journey e.g. Mirza Ghalib, Nazir Akbar Abadi and Amir Khusro etc. After the establishment of Pakistan, children's literature started to show national colors. But in today's era, there is a need to highlight creative and technical skills in children's literature so our children not only cope with the demands of the national but the modern age.